2004
DOI: 10.1080/10428190310001654032
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (Cox-2) Expression in Lymphomas

Abstract: Lymphoma is a malign disease of the lymphoid system. A variety of risk factors have been described in pathogenesis of disease. We investigated the role of Cyclooxygenase-2 (Cox-2) in malign lymphomas. A total of 52 patients who were admitted to the Oncology Unit of Mersin University with histologically diagnosed lymphoma were enrolled to this study. Ten of the patients had Hodgkin's disease (HD), and 42 had non-Hodgkin's lymphoma (NHL). An immunuhistochemical method was used for Cox-2 expression. Cox-2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
3
37
1
Order By: Relevance
“…In a small study, Hazar et al demonstrated that in 70% of Hodgkin's patients' HRS cells expressed Cox-2 [32]. Another study showed that HRS cells from nearly half of patients screened expressed Cox-2 and this was associated with increased proliferation and malignant cell survival [3].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a small study, Hazar et al demonstrated that in 70% of Hodgkin's patients' HRS cells expressed Cox-2 [32]. Another study showed that HRS cells from nearly half of patients screened expressed Cox-2 and this was associated with increased proliferation and malignant cell survival [3].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%
“…More recent studies have shown that patients whose lymphomas expressed Cox-2 were more likely to have aggressive tumor growth. In one study, 57% of patients expressed Cox-2 in their non-Hodgkin's lymphoma cells [32]. Cox-2 expression was determined through immunohistochemical analysis and was further correlated with poor response to chemotherapy.…”
Section: Non-hodgkin's Lymphomamentioning
confidence: 99%
“…Several cytokines, chemokines and inflammatory enzymes are known to induce COX-2 expression. [53][54][55] The data analysis presented above for COX-2 staining intensity show for the first time that COX-2 expression can independently predict prostate cancer recurrence. The sensitivity, specificity and accuracy of COX-2 staining to predict biochemical recurrence Note that 62 months, 72 months and 100 months were used as a cut point for determining biochemical recurrence.…”
Section: Determination Of Sensitivity Specificity Accuracy Ppv Andmentioning
confidence: 99%
“…For example, in non-Hodgkin's lymphoma, high COX-2 expression correlates with increased stage, lower survival and lower complete response rate to therapy. 55 In breast cancer, COX-2 overexpression occurs in 43% of human invasive breast cancers and 63% of ductal carcinomas in situ. 57,58 Furthermore, high expression of COX-2 associates with decreased disease specific survival.…”
Section: Determination Of Sensitivity Specificity Accuracy Ppv Andmentioning
confidence: 99%
“…A recent study also demonstrated that patients with Hp + early-stage DLBCL could achieve complete pathological remission via Hp eradication (22). Studies have found that there is a clinical correlation between COX-2 expression and prognostic factors in lymphoma patients (23)(24)(25), and that IL-32 is also closely linked with T-cell lymphoma and Hp + gastritis (12,26). However, the expression of COX -2 and IL-32, …”
Section: Discussionmentioning
confidence: 99%